2014
DOI: 10.1021/ci5001955
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Validated hERG Pharmacophore Models as Cardiotoxicity Prediction Tools

Abstract: The goal of this study was to design, experimentally validate, and apply a virtual screening workflow to identify novel hERG channel blockers. The hERG channel is an important antitarget in drug development since cardiotoxic risks remain as a major cause of attrition. A ligand-based pharmacophore model collection was developed and theoretically validated. The seven most complementary and suitable models were used for virtual screening of in-house and commercially available compound libraries. From the hit list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 69 publications
2
56
0
Order By: Relevance
“…Those fragments offer particularly valuable information for the compound design and avoiding undesirable hERG activity. The authors have noted that the positive ionizable nitrogen is beneficial for ligand–hERG interaction, in agreement with Kratz's previous work on pharmacophore models, and that increased hydrophobicity is correlated with increased hERG binding. Although many prediction models of hERG blockers have been developed, there are still some problems, including the unclear mechanism of hERG inhibition and the uncertainty of experimental data.…”
Section: Computational Methods For Cbddsupporting
confidence: 86%
“…Those fragments offer particularly valuable information for the compound design and avoiding undesirable hERG activity. The authors have noted that the positive ionizable nitrogen is beneficial for ligand–hERG interaction, in agreement with Kratz's previous work on pharmacophore models, and that increased hydrophobicity is correlated with increased hERG binding. Although many prediction models of hERG blockers have been developed, there are still some problems, including the unclear mechanism of hERG inhibition and the uncertainty of experimental data.…”
Section: Computational Methods For Cbddsupporting
confidence: 86%
“…c), where the aromatic interactions are like the handle and the nitrogen feature is placed along the length of the plug. Kratz et al . constructed a pharmacophore model (Fig.…”
Section: Small Molecule Features and Herg Blockadementioning
confidence: 99%
“…A large number of studies 14,42,47,51,[126][127][128] have reported different pharmacophore features of hERG blockers and computational predictive models based on the structure properties r KALYAANAMOORTHY AND BARAKAT of the ligands. Some of the previously reported predictive models are summarized in Table III.…”
Section: A Pharmacophore and Sar Modelsmentioning
confidence: 99%
“…Recently, Kratz et al [45] reported a study using the combination of two pharmacophore methods: Catalyst (Accelrys Software Inc.) and LigandScout [46]. Ten Catalyst models were built based on 18 hERG inhibitors and validated using a set of 19 inhibitors, Table 2.…”
Section: Pharmacophore Modelsmentioning
confidence: 99%